DIGITALIZATION OF PUBLIC FINANCE FOR ENHANCING STATE TRANSPARENCY AND ACCOUNTABILITY - Качула, Світлана (Modern engineering and innovative technologies, 2025)
The article is devoted to the study of digitalization of public finance as a key factor in enhancing transparency and government accountability. It analyzes the theoretical and methodological foundations of the digital transformation of the budgetary proc